2003
DOI: 10.1097/01.asn.0000045049.72965.b7
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril and Losartan Reduce Sympathetic Hyperactivity in Patients with Chronic Renal Failure

Abstract: Abstract. The aim of this study was to compare the effects on BP and sympathetic activity of chronic treatment with an angiotensin (Ang)-converting enzyme (ACE) inhibitor and an AngII receptor blocker in hypertensive patients with chronic renal failure (CRF). In ten stable hypertensive CRF patients (creatinine clearance, 46 Ϯ 17 ml/min per 1.73 m 2 ), muscle sympathetic nerve activity (MSNA), plasma renin activity (PRA), baroreceptor sensitivity, and 24-h ambulatory BP were measured in the absence of antihyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 27 publications
3
129
1
3
Order By: Relevance
“…Indeed, the patients of this study had increased PRA. Previously, we demonstrated that an ACE inhibitor and an angiotensin II receptor antagonist reduce sympathetic overactivity, strongly suggesting that angiotensin II importantly contributes in the pathogenesis of the sympathetic hyperactivity (5,23).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the patients of this study had increased PRA. Previously, we demonstrated that an ACE inhibitor and an angiotensin II receptor antagonist reduce sympathetic overactivity, strongly suggesting that angiotensin II importantly contributes in the pathogenesis of the sympathetic hyperactivity (5,23).…”
Section: Discussionmentioning
confidence: 93%
“…They include, for example, angiotensin II, which 1) enhances neuroadrenergic cardiovascular drive through stimulation of receptors located within the hypothalamus (paraventricular nucleus) (38), 2) interacts with the nitric oxide system to potentiate sympathetic function (38, 39) and 3) affects norepinephrine turnover at the level of peripheral nerve endings (40). This hypothesis appears to be confirmed also in humans by the evidence that in obese hypertensive patients, patients with renal insufficiency, or patients with left ventricular failure (i.e., in conditions characterized by a marked sympathetic and reninangiotensin activation), administration of angiotensin II receptor blockers results in a clearcut sympathoinhibition (41)(42)(43). A further hormonal substance is leptin, which acts at the level of the hypothalamus to increase blood pressure via its central sympathoexcitatory effects (44,45).…”
Section: Fig 5 Muscle Sympathetic Nerve Traffic Values In Control Ementioning
confidence: 94%
“…A recent study showed that the combination of losartan and hydrochlorothiazide provided greater reductions in clinic and ambulatory BP than hydrochlorothiazide or losartan monotherapy. 13 It was reported recently that losartan decreased MSNA in hypertensive patients with chronic renal failure, 14 whereas administration of hydrochlorothiazide alone for 12 weeks did not affect MSNA in obese hypertensive individuals. 11 We thereby reasoned that administration of Hyzaar may decrease MSNA in hypertensive patients, which would suggest resetting of sympathetic baroreflex function associated with control of BP.…”
mentioning
confidence: 96%